A Novel Polyherbal Formulation Modulates Cyclophosphamide-Induced Cytotoxicity in TM3 Leydig Cells and Delays Fictive Ejaculation in Spinal Cord Transected Male Rats - Patrick Brice Defo Deeh; Hye-Yong Kim; Kiseok Han; Anbazhagan Sathiyaseelan; Hyun-Jong Cho; Myeong-Hyeon Wang (Pharmaceuticals, 2025)
Background: Cyclophosphamide (CP) chemotherapy is commonly associated with various side effects. The development of an effective therapy capable of counteracting these effects is of great interest. Objectives: We evaluated the effects of a novel polyherbal formulation (PHF) on CP cytotoxicity in TM3 cells and fictive ejaculation in rats, and determined its possible mechanism. Methods: The phytochemical analysis of PHF was determined by GC-MS. Various oxidative stress-related parameters (DPPH, ABTS+, CUPRAC, FRAP, MMP, and DCF-DA) and the cytotoxicity (hemolysis and HET-CAM) of PHF were evaluated. Its effect on fictive ejaculation was tested by recording the electromyographic activities of bulbospongiosus muscles, and the involvement of TRPV1/TRPM2 channels was investigated using their specific agonists and antagonists. Results: We found that PHF contained various phytocompounds. PHF prevented CP-induced oxidative stress in TM3 cells, probably due to its strong antioxidant potential. For instance, PHF inhibited apoptosis, lipid peroxidation, and ROS generation. Furthermore, the activities of capsaicin (CAP) and cumene hydroperoxide (CHPx) were significantly lowered by PHF, indicating TRPV1 and TRPM2 inhibition. In the in vivo study conducted in spinal male rats, the number of contractions of the bulbospongiosus muscles was significantly (p < 0.001) lowered in the PHF + DOPA (1.54 ± 0.3) and PHF + CAP (2.43 ± 0.74) groups, compared with the DOPA (8.75 ± 0.71) and CAP (7.41 ± 1.01) groups, respectively. Additionally, PHF delayed the pro-ejaculatory effects of dopamine (by 17.6%) and capsaicin (by 32.69%). The in silico study revealed a strong binding affinity between the selected PHF phytocompounds and the active pockets of TRPV1 and TRPM2. HET-CAM and hemolysis assays revealed no harmful effects of PHF. Conclusions: PHF prevented CP cytotoxicity in TM3 cells and delayed the pro-ejaculatory effects of dopamine and capsaicin in spinal rats through dopamine and TRPV1 inhibition. PHF could be a potential candidate for the management of CP chemotherapy-related disorders, such as premature ejaculation, in particular.